70 - 5(x - 3) = 45
-5(x - 3) = 45 - 70
-5(x - 3) = -25
x - 3 = (-25) : (-5)
x - 3 = 5
x = 5 + 3
x = 8
Trả lời:
\(70-5\times\left(x-3\right)=45\)
\(\Leftrightarrow5\times\left(x-3\right)=25\)
\(\Leftrightarrow x-3=5\)
\(\Leftrightarrow x=8\)
Vậy \(x=8\)
70 - 5 x ( x - 3 ) = 45
5 x ( x - 3 ) = 25
x - 3 = 5
x = 8
Vậy x = 8
5×(x-3)=70-45
5×(x-3)=25
(x-3)=25:5
(x-3)=5
x=5+3
x=8
vậy x=8
\(70-5\times\left(x-3\right)=45\)
\(5\left(x-3\right)=70-45\)
\(5\left(x-3\right)=25\)
\(x-3=25:5\)
\(x-3=5\)
\(x=5+3=8\)
Học tốt
\(70-5\left(x-3\right)=45\Leftrightarrow70-5x+15=45\)
\(\Leftrightarrow85-5x=45\Leftrightarrow40-5x=0\)
\(\Leftrightarrow5x=40\Leftrightarrow x=8\)